Assessment of eye care practices and health belief model factors among adult intensive care unit nurses in public hospitals of Amhara Region, Ethiopia - Abebe Dilie Afenigus; Helen Asmamaw Asres (BMC, 2024)
Abstract Background Eye care is a vital aspect of overall patient health, especially in intensive care units (ICUs) where patients face a heightened risk of ocular complications. Approximately 60% of patients with tracheal tubes and lagophthalmos develop severe ocular surface diseases, such as corneal abrasions, conjunctivitis, and exposure keratopathy, due to insufficient eye protection and lubrication. These complications can adversely affect patient outcomes, including increased mortality rates, extended hospital stays, and reduced satisfaction with care. Despite the importance of effective eye care, practices among intensive care unit nurses can be inconsistent, often influenced by their beliefs and perceptions. The Health Belief Model (HBM) offers a framework to understand these influences, highlighting how nurses' attitudes toward eye care are shaped by their perceptions of patient severity, susceptibility to complications, perceived benefits and barriers to care, cues to action, and self-efficacy. Objective This study aims to assess eye care practices among adult intensive care unit nurses in public hospitals in the Amhara Region of Ethiopia and to identify factors influencing these practices based on the Health Belief Model. Methods A facility-based cross-sectional study was conducted among 213 nurses working in adult ICUs using simple random sampling. Data were collected through a structured, self-administered questionnaire and an observation checklist utilizing Kobo Collect. The data were analyzed using SPSS. Bivariable and multivariable logistic regression models were employed to identify relationships between the constructs of the Health Belief Model and eye care practices. Results In this study, 213 of the 222 respondents participated, resulting in a 96% response rate. Among the participants, 113 nurses (53.1%; 95% CI: 46.5-59.6) demonstrated a high likelihood of providing eye care, while 100 nurses (46.9%; 95% CI: 40.4-53.5) exhibited a lower likelihood based on constructs of the Health Belief Model. Additionally, 125 nurses (58.7%; 95% CI: 52.1-65.3) had inadequate eye care practices, while 133 (62.4%; 95% CI: 55.4-69) possessed adequate knowledge about eye care. Furthermore, 113 participants (53.1%; 95% CI: 46-60.1) held a favorable attitude toward eye care. The multivariable analysis identified several factors associated with eye care practices: monthly salary (AOR = 2.4, 95% CI: 1.1-5.7), educational level (AOR = 0.2, 95% CI: 0.06-0.8), knowledge of eye care (AOR = 2, 95% CI: 1.1-3.4), and availability of eye care equipment (AOR = 0.3, 95% CI: 0.1-0.5). Conclusion and recommendation The study reveals that fewer than half of the nurses working in adult intensive care units in public hospitals in the Amhara region provide adequate eye care, despite a strong intention to do so. Key factors influencing eye care practices include monthly salary, knowledge level, educational qualifications, and the availability of necessary equipment. To improve eye care delivery, it is essential for relevant authorities to implement targeted training and educational initiatives for nurses, thereby enhancing their skills and knowledge in eye care practices.